Livelihoods and rural wealth distribution among farm households in western Kenya : Implications for rural development, poverty alleviation interventions and peace - Chianu, Jonas N.; Ajani, OIY (2008)
The study examined livelihoods and wealth distribution among farm households in western Kenya. Stratified random sampling was used to select 252 households from eight districts. Focus group discussions were used to collect complementary community-level data. Results indicate that average household size was seven persons. The cropping system was over 70% mixed. Agriculture was the main source of livelihoods. Labour was mainly allocated to crop enterprises, with household heads allocating > 50% of their labour to it. Maize (Zea mays) and common beans (Phaseolus vulgaris) were the most important staple/traded food crops. Poultry, followed by cattle dominated livestock enterprises. Few households diversified into small businesses, employment and artisan to enhance livelihoods. Despite this, 5 – 95% of people remained food insecure. Lack of cash and limited land access were the most important factors constraining agricultural development. Although, most households preferred selling produce in markets where prices were better, many not only sold produce but purchased inputs from nearest towns due to high costs of accessing better price markets. Wealth inequality among households was very high, with household wealth Gini-coefficient of 0.52 and per capita wealth Gini-coefficient of 0.55, calling for better interventions targeting to reach most vulnerable/marginal groups and create all-inclusive opportunities.